Influence of cytochrome P450 polymorphisms on the antiplatelet effects of prasugrel in patients with non-cardioembolic stroke previously treated with clopidogrel - Kitazono, Takanari (J Thromb Thrombolysis, 2018)
This randomized double-blind crossover study aimed to investigate the influence of cytochrome P450 (CYP) 2C19 polymorphisms on the antiplatelet effects of prasugrel in patients with non-cardioembolic stroke treated with clopidogrel. Patients received clopidogrel 75 mg/day for > 4 weeks. Subsequently, patients received prasugrel 3.75 mg/day (group A; n = 64) or 2.5 mg/day (group B; n = 65) for 4 weeks followed by a 4 week switched-dose regimen. To assess the influence of CYP2C19 polymorphisms, patients were classified as extensive metabolizers (EMs), intermediate metabolizers (IMs), and poor metabolizers (PMs). The primary endpoint was P2Y(12) reaction units (PRU) at the end of each 4 week treatment. A significant reduction in PRU was noted after treatment with prasugrel 3.75 mg/day compared with the pre-dose value (after treatment with clopidogrel) (p < 0.0001). By CYP2C19 phenotypes, a significant reduction in PRU was noted in IMs and PMs after treatment with prasugrel 3.75 mg/day and in PMs after treatment with prasugrel 2.5 mg/day, as compared with the pre-dose value (p < 0.0001). The plasma concentration of the active metabolite of clopidogrel was relatively low in PMs compared to EMs and IMs; prasugrel was similar across all CYP2C19 phenotypes. No major or clinically significant hemorrhagic adverse events occurred. By CYP2C19 phenotype, the antiplatelet effects of prasugrel were greater with 3.75 mg/day in IMs and PMs, and with 2.5 mg/day in PMs compared with clopidogrel 75 mg/day, without safety concerns. CYP2C19 polymorphisms did not affect the plasma concentration of the active metabolite of prasugrel or its antiplatelet effects. (JapicCTI-101044). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11239-018-1714-2) contains supplementary material, which is available to authorized users.